Results of experimental studies on suppressing the growth of micromycetes (fam. Saprolegniaceae) on egg membranes of embryos of russian sturgeon and beluga in the incubation period - V. V. Barinova; A. A. Bahareva; M. E. Perunova (Известия ТИНРО, 2022)
For successful development of aquaculture, fish farms have to be provided by effective means and methods to prevent and treat diseases of fish. Many drugs are limited for using in aquaculture, so the influence of each particular drug or chemical substance on the fish development should be investigated carefully. Effectiveness of chemical solutions for suppressing the growth of saprolegnium micromycetes on egg membranes and other tissues of sturgeon embryos during their incubation is evaluated. The experiment was conducted at the research and experimental base BIOS belonged to the Russian Res. Inst. of Fisheries and Oceanography, Volga-Caspian branch (CaspNIRKh) located in Astrakhan and included a series of observations on incubation of sturgeon eggs processed with solutions of some chemicals (Purple-K, sodium chloride, hydrogen peroxide) or drug (Iodinol). Two sturgeon species (russian sturgeon and beluga) were tested with measuring biological parameters of their embryos, as survival rate, contamination by saprolegnia micromycetes, number of abnormally developing embryos, and number of obtained prelarvae. The processing with 0.05 % solution of hydrogen peroxide (10 min. exposure) and with 0.90 % solution of sodium chloride (3 min. exposure) showed the best results: these solutions made the lowest negative effect on the embryos survival but reduced significantly infection of incubated eggs.